Investigating the potentially important role of psychological flexibility in adherence to antiretroviral therapy in people living with HIV. Issue 3 (4th March 2021) - Harrison, Anja; Scott, Whitney; Timmins, Liadh; Graham, Christopher D.; Harrison, Anthony M.
ABSTRACT: Antiretroviral therapy (ART) has significantly improved immune health and survival rates in HIV, but these outcomes rely on near perfect adherence. While many psychosocial factors are related to sub-optimal adherence, effectiveness of associated interventions are modest or inconsistent. The Psychological Flexibility (PF) model underlying Acceptance and Commitment Therapy (ACT) identifies a core set of broadly applicable transdiagnostic processes that may be useful to explain and improve non-adherence. However, PF has not previously been examined in relation to ART adherence. Therefore, this cross-sectional study ( n  = 275) explored relationships between PF and intentional/unintentional ART non-adherence in people with HIV. Adults with HIV prescribed ART were recruited online. Participants completed online questionnaires assessing self-reported PF, adherence and emotional and general functioning. Logistic regressions examined whether PF processes were associated with intentional/unintentional non-adherence. Fifty-eight percent of participants were classified as nonadherent according to the Medication Adherence Rating Scale, of which 41.0% reported intentional and 94.0% unintentional non-adherence. Correlations between PF and adherence were small. PF did not significantly explain intentional/unintentional non-adherence after controlling for demographic and disease factors. Further clarification of the utility of PF in understanding ART non-adherence is warranted using prospective or experimental designs in conjunction with more objective adherence measures.